Antihypertensive Effects of Black Cincau (Mesona palustris BL) Effervescent Powder and Malondialdehyde Concentration on Wistar Rats as a Hypertensive Model - Tri Dewanti Widyaningsih; Novita Wijayanti; Dian Handayani; Guntur Prasetyo (Research Journal of Life Science, 2016)
This study investigated the effects of Black cincau (Mesona palustris BL) effervescent powder (BCEP) on systolic blood pressure and malondialdehyde concentration in hypertensive rats. BCEP were orally administered to hypertensive rats for 4 weeks, and antihypertensive effects were determined. Rats were given 630 mg/kg, 1.260 mg/kg and 1.890 mg/kg BCEP on dose group 1, 2, 3 respectively. These groups were  compared with a negative control group, hypertensive control group and Captopril control group. These results showed that systolic blood pressure and MDA concentrations of rats dosed with BCEP were significantly different (α=0,01) to those of control rats. Rats dose third group with of 1.260 mg/kg showed the highest percentage of lowering blood pressure. The rat dose third group had highest percentage decreased in systolic blood pressure (43,97%) and in MDA concentration (68,77%).Key words : Antihypertensive; Black Cincau (Mesona palustris BL) Effervescent Powder; Malondialdehyde